Effect of Tax Incentives and Non-Tax Incentives on Earnings Management with Tax Avoidance as a Variable Moderation - I Gusti Agung Daniya Ariyanti Rahayu; I W Karmana; I W Purwanta Suta (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Tax incentives and non-tax incentives are both potential motivators for earnings management activity. As a result, the study was conducted to determine the reality of various aspects that could effect profits management. It also conducted tests to demonstrate the impact of tax avoidance on the relationship between the research variables. This research employed secondary data from the Indonesia Stock Exchange for the year 2020, as well as a purposive sampling strategy to select the appropriate firm to serve as the sample. To aid in the testing of the variables, this study used the multiple linear regression model as an analysis tool utilizing IBM SPSS version 25. The findings suggest that tax incentives can be used to detect profits management, as measured by a proxy of tax planning and deferred tax expense. Non-tax incentives, on the other hand, cannot be used to predict earnings management if the proxy is based on the profitability ratio and the amount of managerial ownership. Meanwhile, tax evasion can only amplify the impact of present taxes on earnings management, which includes variables such as tax incentives.